Body type and performance of elite Cuban baseball players - Carvajal, W.; Rios, A.; Echevarria, I.; Martinez, M.; Minoso, J.; Rodriguez, D. (MEDICC Review, 2009)
Appropriate stature and adequate somatotype are not the only attributes determining athletic performance, but they are important prerequisites for sports participation and success. However, there is scant literature on baseball players` kinanthropometric profiles and their association with performance. Given that Cuban baseball players have been among the world`s top performers in recent decades, characterization of their morphological features linked to their performance may contribute to developing the evidence base in this area. Objective: Describe the kinanthropometric profile related to sports performance of elite Cuban baseball players, classified by playing position. Methods: Body composition, somatotype, proportionality, and performance were measured in 100 elite baseball players grouped by playing position and performance. Data from the 2002-2003 baseball season was gathered for players participating in the 43rd Cuban National Baseball Series (November 2003-May 2004). Slugging percentage (SLG) was used to measure performance of all players except pitchers, whose performance was measured as end-of-season win-loss record. Mean and standard deviation values were calculated for anthropometric and performance results, presented in tables for comparison. ANOVA and MANOVA analyses were applied to determine magnitudes of difference between the variables studied, as well as statistical significance of the differences established (p=0.05 and p=0.01). Results: Performance and body type varied by playing position, and statistically significant differences were found in performance, body composition and somatotype variables between some positions. No significant differences in proportionality were found. First basemen and outfielders (center, left, and right fielders) were the best offensive players with the highest mean SLG, body weight and muscle mass values. Infielders (second basemen, shortstops, and third basemen) had the lowest mean body weight and adipose tissue mass values, as well as the lowest mean SLG. Catchers had similar mean weight, height, muscle mass, and adipose tissue mass values as first basemen, outfielders and infielders, but a low mean SLG similar to that of infielders. Pitchers were morphologically similar to players in all positions, but significant morphological differences were found among pitchers with different performance levels. Better-performing pitchers (=.600 winning percentage (Wpct)) were significantly heavier and more mesomorphic than lower-performing pitchers (<.600 Wpct). All players were predominantly mesoendomorphic, but mean somatotype values varied between players in different positions, and between pitchers with different performance levels. Conclusions The kinanthropometric profile of high-performance baseball players described in this study generally coincides with the available literature. Further research on comparative samples is needed to validate the relationship between players` body type and performance. Nevertheless, the results of this study may be applied to criteria for selection and training of high-performance baseball players in Cuba.